2023
DOI: 10.3390/ijms24021089
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related microRNA Overexpression in Lafora Disease Male Mice Provides Links between Neuroinflammation and Oxidative Stress

Abstract: Lafora disease is a rare, fatal form of progressive myoclonus epilepsy characterized by continuous neurodegeneration with epileptic seizures, characterized by the intracellular accumulation of aberrant polyglucosan granules called Lafora bodies. Several works have provided numerous evidence of molecular and cellular alterations in neural tissue from experimental mouse models deficient in either laforin or malin, two proteins related to the disease. Oxidative stress, alterations in proteostasis, and deregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Both miR-155 and miR-146a have been shown to be involved in complementary regulatory pathways activated during the inflammatory response, being the first pro-inflammatory and the second anti-inflammatory [ 53 ]. We showed that both miRNAs are overexpressed, in an age-dependent manner in brains from Epm2a-/- and Epm2b-/- mice models [ 30 ]. Interestingly, this overexpression coincided with the increased expression of putative target genes involved in the inflammatory cascade and oxidative stress responses, such as Sod2 , Socs1 and Traf6 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both miR-155 and miR-146a have been shown to be involved in complementary regulatory pathways activated during the inflammatory response, being the first pro-inflammatory and the second anti-inflammatory [ 53 ]. We showed that both miRNAs are overexpressed, in an age-dependent manner in brains from Epm2a-/- and Epm2b-/- mice models [ 30 ]. Interestingly, this overexpression coincided with the increased expression of putative target genes involved in the inflammatory cascade and oxidative stress responses, such as Sod2 , Socs1 and Traf6 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that both miRNAs are overexpressed, in an age-dependent manner in brains from Epm2a-/- and Epm2b-/- mice models [ 30 ]. Interestingly, this overexpression coincided with the increased expression of putative target genes involved in the inflammatory cascade and oxidative stress responses, such as Sod2 , Socs1 and Traf6 [ 30 ]. The joint action of both miRNAs has also been detected in systemic lupus erythematosus (SLE) patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation